2005
DOI: 10.1515/bmt.2005.024
|View full text |Cite
|
Sign up to set email alerts
|

Eine Präparationstechnik zur quantitativen Untersuchung SPIO-haltiger Lösungen und SPIO-markierter Zellen in der MRT / A preparation technique for quantitative investigation of SPIO-containing solutions and SPIO-labelled cells by MRI

Abstract: The proposed preparation strategy with a well defined spatial distribution of the magnetic material in an agar gel phantom produced reliable results and appears clearly superior compared to set-ups with randomly distributed material in glass tubes. The diameter of the signal extinction in gradient echo images was significantly affected by the choice of echo time and spatial resolution. The calibration of signal cancellation versus iron concentrations may be valuable to assess SPIO concentrations and possibly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(25 reference statements)
2
6
0
Order By: Relevance
“…Although the transverse relaxation rates correlate with the amount of iron, we observed persistent MR signal alterations, despite a reduction in iron content. This result is consistent with the findings of Pintaske et al, 21 indicating that the diameters of the MRI signal extinction correspond to a logarithmic function that is dependent on the iron concentration and flatten out considerably with high iron concentrations. Furthermore, Pintaske et al 21 and Tanimoto et al 31 provided evidence that the extent of the signal extinction was dependent upon the geometric distribution of the iron particles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although the transverse relaxation rates correlate with the amount of iron, we observed persistent MR signal alterations, despite a reduction in iron content. This result is consistent with the findings of Pintaske et al, 21 indicating that the diameters of the MRI signal extinction correspond to a logarithmic function that is dependent on the iron concentration and flatten out considerably with high iron concentrations. Furthermore, Pintaske et al 21 and Tanimoto et al 31 provided evidence that the extent of the signal extinction was dependent upon the geometric distribution of the iron particles.…”
Section: Discussionsupporting
confidence: 93%
“…21 Briefly, a 1% agar solution (dissolved in PBS) was boiled and slowly cooled in a 37°C water bath to minimize air bubbles that would produce artifacts during MRI. Before congealing, the agar was embedded in specialized plastic boxes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical size of the cell aggregation was presumed to extend over several imaging voxels. Recent studies have shown that labelled cells can aggregate in spherical cluster (Daldrup-Link et al 2003, Jendelova et al 2003, Pintaske et al 2005. Consequently, the present restriction to spherical geometries is no major limitation.…”
Section: General Considerationsmentioning
confidence: 95%
“…The ability of MRI to visualize aggregations of thousands to millions of SPIO-labelled cells has attracted much attention in the past few years (Bos et al 2004, Daldrup-Link et al 2005, Himes et al 2004, Hoehn et al 2002, Jendelova et al 2003. Aggregations of labelled cells are reflected either as low-intensity signal spots or signal voids, particularly in T * 2 -weighted gradient echo MRI (De Vries et al 2005, Hauger et al 2006, Pintaske et al 2005, Zhang et al 2004. It is important to know that localized MR signal loss can be caused by tissue-specific magnetic field inhomogeneities, which mimic the appearance of labelled cells under in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%